Sosialisasi Tanaman Penurun Gula Darah Di Desa Koto Ringin Kecamatan Mempura Kabupaten Siak - Radith Mahatma; Dyah Iriani; Yusfiati, Yusfiati; Nery Sofiyanti; Roza Elvyra; Fadel Nugraha (LPPM UMRI, 2024)
Negative impact of the development over time in the health aspect is the change in lifestyle or unhealthy dietary habits, particularly through the consuming of instant foods, which can trigger diabetes. Excessive sugar consumption can lead to increasing weight and blood sugar levels, and potentially cause type-2 diabetes (DM). The community of Koto Ringin Village has developed a family medicinal plant program (TOGA) as part of a strategy to improve community health. This program demonstrates proactive steps in addressing health challenges in Koto Ringin Village, both through disease management and community-based health initiatives like TOGA. The purpose of this community service is to improve the understanding of the PKK (Family Welfare Movement) members of Koto Ringin Village by educating them about plants that are useful for lowering blood sugar levels. This community service is also intended for transferring knowledge from the academic environment to the community at large, especially to the members of PKK Koto Ringin Village, Mempura District, Siak Regency, Riau Province. This activity was attended by 18 women from the PKK of Koto Ringin. The results of the activity showed that the participants’ knowledge improved from 41.1 to 90.0.